Taine: An Investigator of Creative Work in Art - Gaižutis, Algirdas (Problemos, 1981)
Aesthetic views by Hippolyte Taine, a French philosopher and most prominent representative of positivism in the 19th century, are discussed. The relations of Taine’s Views both to the tradition of the 19th century idealistic philosophy and to the ideas of positivism are revealed. The author of the article emphasizes the significance of Taine’s aesthetic principles in the formation of art sociology. Consistently defending the theory of social interdependence of art, Taine was a supporter of its contextual interpretation. The methodology of positivism, however, is found to be the obstacle that conditioned his understanding of the historical conditionality of creative work in art as well as the change of values and styles of the latter. Underestimation of the artist’s individuality, taking it as a secondary factor derived from social environment, is considered the major shortcoming of Taine’s theory.